Relationship between Tetracyclines’ Structure and Minimal Inhibitory Concentration of Streptococcus spp. - Marczak, M.; Grabowski, T.; Feder, M. (Drug Research, 2015)
During the past years, a growing number of bacterial strains have become resistant to tetracyclines. The problem of increasing resistance and lack of susceptibility to tetracyclines applies to strains isolated from both: animals and humans. Basic tools to design new drugs and determining the direction of the search for new molecules is the analysis of the relationship between the chemical structure and the pharmacokinetic and pharmacodynamic parameters. Purpose of this study is to determine the relationship between physicochemical parameters of tetracyclines and MIC50 and MIC90 values determined for Streptococcus spp. Analysis of physicochemical parameters of selected drugs was made using MarvinSketch 5.11.5 (ChemAxon Ltd.) and QuickProp 3.1 software from Schrödinger package v 31207. MIC50 and MIC90 values were correlated with 51 calculated physicochemical parameters and arithmetic expressions. Internal and external model validation was performed using leave-one out method. 4 arithmetic expressions fulfilled all validation criteria, but only in relation to MIC50. A new method to optimize the tetracyclines’ structure in relation to Streptococcus spp. was presented. It was also shown that the relations of structure: antimicrobial activity type can have different nature depending on MIC50 or MIC90 of specific bacterial strain.
Keywords: in silico; MIC; tetracycline; validation; structure